1987
DOI: 10.1159/000163390
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of MCF-7 Human Breast Cancer Cell after Prostaglandins PGA<sub>1</sub> and PGF<sub>2α‘</sub>Treatment

Abstract: Treatment of monolayer cultures of MCF-7 cells with prostaglandins PGA1 and PGF inhibited cell proliferation, reduced the rate of labeled precursor incorporation into DNA, RNA, and protein, and induced morphological changes in a dose-dependent manner. The rate of [3H]thymidine incorporation was increased by PGA1 at l0–10–l0–8M, while a sharp decrease was observed at 10–6–10–4 M(p < 0.05 and p < 0.005). PGF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Akt kinase activation also coincided with Akt-dependent proliferation in MCF-7 cells treated with 1–10 µM Δ12-PGJ 2 ( Figure 4B ) . This finding is consistent with reported bi-phasic actions of cyPGs, whereby they increase proliferation of cultured cells at ∼1 µM [37] , [38] , while they decrease proliferation or cause apoptosis by modifying other protein targets at ∼50 µM [39] .…”
Section: Resultssupporting
confidence: 92%
“…Akt kinase activation also coincided with Akt-dependent proliferation in MCF-7 cells treated with 1–10 µM Δ12-PGJ 2 ( Figure 4B ) . This finding is consistent with reported bi-phasic actions of cyPGs, whereby they increase proliferation of cultured cells at ∼1 µM [37] , [38] , while they decrease proliferation or cause apoptosis by modifying other protein targets at ∼50 µM [39] .…”
Section: Resultssupporting
confidence: 92%
“…These cytostatic effects can be reversible, but higher concentrations are cytotoxic and induce apoptosis (4,6,7). Interestingly, at very low concentrations, PGA was found to stimulate cellular proliferation (8). CP-PGs can also activate nuclear peroxisome proliferator-activated receptor-␥ and suppress macrophage activation and inflammatory responses (9 -11).…”
Section: Cyclopentenone (Cp)mentioning
confidence: 99%
“…However, the nature of their effect appears to be cell type-and dose-dependent. Although antiproliferative or proapoptotic effects have been most frequently described (14), CyPG have also been found to induce cell proliferation in mesangial (15), breast cancer (16), and COX-2-depleted colorectal cancer cells (13) when used at nanomolar or low micromolar concentrations. It has been reported that 15d-PGJ 2 can cause the activation of the mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase (ERK) 1͞2 (17)(18)(19), and that phosphatidylinositol 3-kinase (PI3-kinase) inhibitors reduce 15d-PGJ 2 -elicited cell proliferation (15).…”
mentioning
confidence: 99%